Physiological Studies of Glutamine Synthetases I and III from Synechococcus sp. WH7803 Reveal Differential Regulation - Domínguez-Martín, María Agustina; Díez, Jesús; García-Fernández, José M. (Frontiers in Microbiology, 2016)
The marine picocyanobacterium Synechococcus sp. strain WH7803 possesses two glutamine synthetases (EC 6.3.2.1), GSI encoded by glnA and GSIII encoded by glnN. This is the first work addressing the physiological regulation of both enzymes in a marine cyanobacterial strain. The increase of GS activity upon nitrogen starvation was similar to that found in other model cyanobacteria. However, an unusual response was found when cells were grown under darkness: the GS activity was unaffected, reflecting adaptation to the environment where they thrive. On the other hand, we found that GSIII did not respond to nitrogen availability, in sharp contrast with the results observed for this enzyme in other cyanobacteria thus far studied. These features suggest that glutamine synthetase activities in Synechococcus sp. WH7803 represent an intermediate step in the evolution of cyanobacteria, in a process of regulatory streamlining where GSI lost the regulation by light, while GSIII lost its responsiveness to nitrogen. This is in good agreement with the phylogeny of Synechococcus sp. WH7803 in the context of the marine cyanobacterial radiation.